Composite resonant cavity structure of MDM nano-cavity coupled two-dimensional transition metal sulfide based on fano resonance and preparation method of composite resonant cavity structure

By coupling two-dimensional transition metal sulfides in the MDM cavity structure and designing a composite resonant cavity structure, the problems of narrow Fano resonance tunable range and small resonance intensity in the prior art are solved, Fano resonance with high quality factors and strength are achieved, and multi-path regulation capabilities are provided.

CN119882108AActive Publication Date: 2025-04-25ANHUI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411990908.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing MDM cavity structure is too narrow in the tunable range of Fano resonance, and the background reflection spectrum is relatively fixed, making it difficult to achieve better tuning, and the resonance intensity is also small, making it difficult to enter practical applications.

Method used

A composite resonant cavity structure based on Fano resonance of MDM nanocavity coupled with two-dimensional transition metal sulfide is designed to achieve multi-path tunable Fano resonance by adjusting the thickness of the dielectric layer and the uniformity of the metal layer.

Benefits of technology

The quality factor and intensity of Fano resonance are improved, and the resonance wavelength and line width can be accurately adjusted through temperature or dielectric layer thickness, enhancing the device's scalability and application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119882108A_ABST
    Figure CN119882108A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photoelectric regulation and control, and particularly relates to a fano resonance-based MDM nano-cavity coupled two-dimensional transition metal sulfide composite resonant cavity structure and a preparation method thereof. The invention provides a fano resonance-based composite resonant cavity structure of coupling an MDM nano-cavity with a two-dimensional transition metal sulfide, in the MDM nano-cavity, the material of a dielectric layer comprises one or more of hexagonal boron nitride and indium tin oxide, and the two-dimensional transition metal sulfide comprises tungsten disulfide. The MDM nanocavity sequentially comprises a metal layer a, a hexagonal boron nitride layer, an indium tin oxide layer and a metal layer b; and the material of the metal layer comprises one or more of silver, titanium, chromium and gold. According to the invention, an optical film system design thought of coupling the MDM nanocavity with the TMDs atomic layer and an efficient preparation method are adopted, and multi-path tunable optical reflectance spectrum fano resonance is generated. The quality factor and the strength of the Fano resonance are greatly superior to those of other similar structures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photoelectric control, and specifically relates to a composite resonant cavity structure of an MDM nanocavity coupled with a two-dimensional transition metal sulfide based on Fano resonance and a preparation method thereof. Background Art

[0002] In optical reflectivity, Fano resonance is an asymmetric spectral line shape phenomenon caused by the interference between discrete states and continuous states. This phenomenon manifests itself in optical reflectivity as a reflection peak with a specific asymmetry due to the interference between resonant modes when light waves interact with specific structures (such as photonic crystals, waveguides or nanostructures). This asymmetry is caused by the coupling between discrete states (narrowband localization) and continuous states (broadband background), resulting in sharp, asymmetric reflectivity changes near the resonant frequency.

[0003] The MDM cavity, or Metal-Dielectric-Metal cavity, is an optical resonance structure consisting of two metal layers and a dielectric layer sandwiched in between. The MDM cavity exhibits strong optical resonance characteristics, which is mainly due to the excitation of surface plasmons (SPPs) in its structure. The unique optical properties of SPPs make the Fano resonance effect produced by the MDM cavity extremely sensitive to environmental changes. Furthermore, tunable spectral Fano resonance can be achieved by changing one or more structural properties. For example, HUA LU et al. disclosed in "Exciton-induced Fano resonance in metallic nanocavity with tungsten disulfide atomic layer" (Optics Express, 2023, 31 (13), 20761-20768) the weakly coupled Fano resonance and asymmetric spectral response that appear when an ultrathin MDM cavity is integrated with a two-dimensional ultrathin nano transition metal sulfide material (TMDs). The resonant wavelength of the MDM nanocavity can be controlled by adjusting the thickness of the dielectric layer.

[0004] However, this method still has the following shortcomings: the tunable range of Fano resonance is too narrow because the structure is not suitable for applying an external electric field to perform band control engineering on TMDs; and the thickness and optical properties of the metal layer and the dielectric layer are relatively fixed after the device is prepared, so the background reflection spectrum of the MDM cavity is relatively fixed after the device is prepared, and it is difficult to achieve better tuning of the coupling strength of the Fano resonance; in addition, the resonance intensity generated by the above reference method is relatively small and cannot be well applied in practice. Summary of the invention

[0005] In response to the current problems, the present invention provides a new method for optical device design, which utilizes MDM nanocavity coupled to TMDs atomic layer to prepare a composite device structure based on multi-path tunable Fano resonance. The Fano resonance reflection spectrum generated in this way can be used to design metamaterials and metasurface structures with specific optical properties, such as optical switches, bio-chemical sensors, etc.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] The present invention provides a composite resonant cavity structure of an MDM nanocavity coupled with a two-dimensional transition metal sulfide based on Fano resonance, wherein the MDM nanocavity comprises a dielectric layer and a metal layer; the material of the dielectric layer comprises one or more of hexagonal boron nitride and indium tin oxide; and the two-dimensional transition metal sulfide comprises tungsten disulfide.

[0008] Furthermore, the MDM nanocavity includes, in sequence: a metal layer a, a hexagonal boron nitride layer, an indium tin oxide layer, and a metal layer b; the material of the hexagonal boron nitride layer includes hexagonal boron nitride; the material of the indium tin oxide layer includes indium tin oxide; the material of the metal layer a includes one or more of silver, titanium, chromium, and gold; the material of the metal layer b includes one or more of silver, titanium, chromium, and gold.

[0009] Furthermore, the composite resonant cavity structure includes a silver layer a, the hexagonal boron nitride layer, a tungsten disulfide layer, the indium tin oxide layer, and a silver layer b in sequence; the material of the tungsten disulfide layer includes tungsten disulfide; and the materials of the silver layer a and the silver layer b both include silver.

[0010] Furthermore, the thickness of the silver layer a is 5 to 15 nm, the thickness of the hexagonal boron nitride layer is 25 to 75 nm, the thickness of the tungsten disulfide layer is 0.7 to 10 nm, the thickness of the indium tin oxide layer is 8 to 20 nm, and the thickness of the silver layer b is 20 to 50 nm.

[0011] Preferably, the thickness of the hexagonal boron nitride layer is 30-60 nm.

[0012] Preferably, the tungsten disulfide layer includes three WS2 atomic layers.

[0013] Preferably, the thickness of the silver layer a is 8.5 nm.

[0014] Furthermore, the composite resonant cavity structure also includes a silicon wafer substrate; the silicon wafer substrate includes a SiO2 layer attached to one side of the Si layer; the silicon wafer substrate is attached to the outer side of the silver layer b by the SiO2 layer.

[0015] Accordingly, the present invention also provides a method for preparing the above-mentioned MDM nanocavity coupled with a two-dimensional transition metal sulfide composite resonant cavity structure based on Fano resonance, comprising the following steps:

[0016] S1, growing the silver layer b by vacuum evaporation coating method;

[0017] S2, growing the indium tin oxide layer on the surface of the silver layer b by magnetron sputtering coating method;

[0018] S3, preparing the tungsten disulfide layer on the surface of the indium tin oxide layer by a mechanical stripping method;

[0019] S4, preparing the hexagonal boron nitride layer on the surface of the tungsten disulfide layer by a mechanical stripping method;

[0020] S5. Growing the silver layer a on the surface of the hexagonal boron nitride layer by a vacuum evaporation coating method to obtain the composite resonant cavity structure.

[0021] Further,

[0022] Step S3 includes the following steps:

[0023] S3-1, prepare a two-dimensional tungsten disulfide sheet on the surface of the PDMS film,

[0024] S3-2, transferring the two-dimensional tungsten disulfide sheet to the surface of the indium tin oxide layer to obtain the tungsten disulfide layer;

[0025] Step S4 includes the following steps:

[0026] S4-1, prepare a two-dimensional hexagonal boron nitride sheet on the surface of the PDMS film,

[0027] S4-2, transferring the two-dimensional hexagonal boron nitride sheet to the surface of the tungsten disulfide layer to obtain the hexagonal boron nitride layer.

[0028] Further,

[0029] Step S3-1 is specifically as follows: placing a block of tungsten disulfide on an adhesive material, and obtaining a tungsten disulfide layered sheet after repeated adhesion and peeling; then attaching the tungsten disulfide layered sheet to a PDMS film, and peeling off the adhesive material to obtain a two-dimensional tungsten disulfide sheet;

[0030] Step S3-2 is specifically: attaching the PDMS film to the surface of the indium tin oxide layer, so that the two-dimensional tungsten disulfide sheet is attached to the indium tin oxide layer, and when the PDMS film is completely attached to the surface of the indium tin oxide layer, heating the entire layer; then peeling off the PDMS film to obtain the tungsten disulfide layer;

[0031] Step S4-1 is specifically as follows: placing a block of hexagonal boron nitride on an adhesive material, and obtaining a hexagonal boron nitride layered sheet after repeated adhesion and peeling; then attaching the hexagonal boron nitride layered sheet to a PDMS film, and peeling off the adhesive material to obtain a two-dimensional hexagonal boron nitride sheet;

[0032] Step S4-2 is specifically as follows: attaching the PDMS film to the surface of the tungsten disulfide layer, attaching the two-dimensional hexagonal boron nitride sheet to the tungsten disulfide layer, and heating the entire layer when the PDMS film is completely attached to the surface of the tungsten disulfide layer; then peeling off the PDMS film to obtain the hexagonal boron nitride layer.

[0033] Furthermore, in step S3-2 or step S4-2, the overall heating temperature is 60° C., and the overall heating time is 5 minutes.

[0034] Furthermore, in step S1, the growth device is a vacuum evaporation coating device; in step S5, the growth device is a vacuum evaporation coating device; in step S1, the growth rate is lower than 0.5 nm / s, and the growth vacuum is less than 10 -5 Pa; in step S5, the growth rate is lower than 0.5 nm / s, and the vacuum degree of the growth is less than 10 -5 Pa;

[0035] In step S2, the growth equipment is a magnetron sputtering coating equipment; in step S2, the growth conditions include: the atmosphere is pure argon, the vacuum degree is less than 10 -4 Pa, the temperature is 295°C, the sputtering voltage is 40V, and the target material is indium tin oxide; the purity of the target material is 99.99%; the doping ratio of the target material is In2O3:SnO2=9:1.

[0036] Furthermore, in step S1, the silver layer b is grown on a silicon wafer substrate; the thickness of the SiO2 is 250-350 nm; and before step S1, the surface of the silicon wafer substrate is cleaned.

[0037] Furthermore, the silicon wafer substrate is oxidized on one side, and the thickness of the SiO2 (oxide layer) is 285±5 nm; the thickness of the silicon single crystal is 1 mm.

[0038] Further, in step S3-1 or step S4-1, the adhesive material includes a blue film.

[0039] Further, in step S3-1 or step S4-1, peeling off the adhesive material includes peeling off the adhesive material slowly.

[0040] Furthermore, in step S3-2 or step S4-2, the attachment rate / peeling rate of the PDMS film is lower than 5 μm / s, so as to improve the success rate of mechanical transfer.

[0041] Furthermore, the silicon wafer substrate is a single-sided oxidized silicon wafer (SiO2 / Si), and the structure is that a 285±5nm oxide layer, namely a SiO2 layer (component is SiO2), is attached to a silicon single crystal, namely a Si layer (component is Si) on one side.

[0042] Furthermore, the surface flatness of the silicon wafer substrate (the surface where SiO2 contacts the air) is about 2 nm.

[0043] The present invention adopts the optical film system design concept of MDM nanocavity coupling TMDs atomic layer and an efficient preparation method to generate multi-path tunable optical reflection spectrum Fano resonance.

[0044] In optical nanoresonators, the coupling of photons and excitons has always been a research hotspot in this field, and it has important application value and industrialization prospects in spectral control. The composite resonant cavity structure of the present invention is based on a two-dimensional ultra-thin nano transition metal sulfide material (TMDs) coupled metal-dielectric-metal (MDM) nanocavity, and the composite resonant cavity structure generates reflection spectrum Fano resonance. The MDM cavity structure used in the present invention is silver (Ag)-indium tin oxide (ITO)-hexagonal boron nitride (h-BN)-silver (Ag).

[0045] The present invention has developed a new MDM integrated TMDs method, in which the dielectric material in the MDM cavity is replaced with a similar dielectric layer with adjustable optical properties, such as a temperature phase change material, to solve the technical problem that the background reflection spectrum is difficult to tune. If the dielectric material in the MDM cavity uses a material with good conductivity as the dielectric layer, the optical properties such as the spectral background cannot be adjusted due to the fully conductive structure.

[0046] The dielectric layer of the MDM cavity of the present invention is h-BN, which has high optical transmittance and high chemical and physical stability. However, the use of various types of traditional coating methods will cause the atomic layer TMDs exciton absorption effect to be damaged to varying degrees due to various physical and chemical reasons (high temperature, gas pollution, breakdown, etc.), and the maximum can completely disable the TMDs. The present invention uses non-invasive, dry mechanical transfer without external conditions, and the damage to the TMDs material is almost negligible.

[0047] The dielectric layer in the MDM cavity of the composite resonant cavity structure of the present invention uses two layers of ITO / h-BN materials, and the structure after coupling with TMDs is ITO / TMDs / h-BN. Compared with the coupling structure of ITO / TMDs / ITO, the present invention achieves more complex functions and better performance by changing the uniformity and continuity of the metal layer and the dielectric layer, including Fano resonance spectrum intensity, quality factor, resonance line width, etc., and also includes flexibility such as realizing multi-physical field (electric, magnetic, temperature) regulation. On this basis, experiments and theoretical simulations can be used to further improve the scene applicability / economy / stability / performance of the structure.

[0048] The following aspects are considered in the selection of TMDs and structural design: TMDs have atomic-level flatness and thickness; TMDs have a strong exciton effect at room temperature - only when the exciton binding energy is large can an absorption peak of sufficient intensity be generated to produce Fano resonance through coupling to the MDM cavity; after coupling, it has a tunable electronic band structure - by changing the temperature / chemical composition, or applying an external electric field, its band structure can be adjusted and the electronic and optical properties can be changed to produce tunable Fano resonance; the layer-dependent optical and electronic properties provide a certain degree of flexibility for designing and optimizing devices.

[0049] Regarding preparation: the intensity of Fano resonance in the prior art has not reached a very high level, because TMDs have not yet reached the ideal exciton absorption intensity. The present invention finds a more optimal preparation process through experiments and simulations; the ITO layer of the present invention is prepared by magnetron sputtering, and its surface flatness is between 2 and 5 nanometers, which makes the step of transferring atomic layer TMDs to the ITO layer difficult to implement. The present invention solves this problem by optimizing the parameters and performance of the magnetron sputtering equipment; the overall preparation of the device is relatively complex. Since the preparation and integration process of the ultra-thin nano multilayer structure is complicated, the present invention solves this problem by optimizing the preparation and integration process as well as optimizing the device structure.

[0050] In summary, in response to the above problems in the field of nanophotonics, the present invention proposes an innovative spectral control scheme. The present invention creatively designs a new optical resonant cavity device structure, integrates atomically thin tungsten disulfide (WS2) into a metal-dielectric-metal (MDM) nanocavity, and successfully achieves precise control of Fano resonance. The high consistency between the experimental results and the numerical simulations confirms the existence of a tunable asymmetric Fano resonance spectrum, which is completely consistent with theoretical predictions.

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] 1. The quality factor and intensity of the Fano resonance in the reflection spectrum generated by the composite resonant cavity structure of the MDM nanocavity coupled with two-dimensional transition metal sulfide based on Fano resonance in the present invention are ahead of other similar structures.

[0053] 2. Based on the discovery that the resonance wavelength, line width and quality factor (q-factor) can be precisely controlled by temperature or the thickness of the MDM cavity dielectric layer, the present invention realizes the precise control of Fano resonance by controlling the thickness of the dielectric layer; at the same time, the multi-physical field spectral simulation of the two-dimensional atomic layer TMDs coupled to the MDM cavity under different conditions further confirms that the composite resonant cavity structure of the MDM nanocavity coupled to the two-dimensional transition metal sulfide based on Fano resonance of the present invention has excellent scalability, laying a solid foundation for future industrial applications.

[0054] 3. The real-time tunability of Fano resonance in the composite resonant cavity structure of the MDM nanocavity coupled with two-dimensional transition metal sulfide based on Fano resonance is proposed in a groundbreaking way, which opens up a new path for optically tunable Fano resonance. The present invention creates a new way for the integration of more complex and miniaturized Fano resonance multi-field tuning systems by integrating various materials with adjustable optical properties.

[0055] 4. The total thickness of the composite resonant cavity structure of the MDM nanocavity coupled with two-dimensional transition metal sulfide based on Fano resonance of the present invention is at the level of 100 nanometers. At this nanoscale level, the integrable characteristics of the device are effectively utilized, and the performance of the device is optimized by longitudinal (vertical stacking) and lateral (horizontal integration) expansion to achieve better performance parameter indicators and flexibility.

[0056] 5. The Fano resonance generated by the composite resonant cavity structure of the MDM nanocavity coupled with two-dimensional transition metal sulfide based on Fano resonance of the present invention can improve spectral resolution and sensing sensitivity, and play an important role in optical modulation, filtering, enhanced spectrum, non-reciprocal light transmission and other fields.

[0057] 6. The present invention has a high degree of integration with the prior art, and the technical preparation process of the composite resonant cavity structure of the present invention is relatively mature, so the sample preparation process can be standardized and streamlined, making it easier for technicians to prepare. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 The preparation process and test analysis flow chart of the composite resonant cavity structure of the present invention;

[0059] Figure 2 The preparation process and flow of each layer of the composite resonant cavity structure of the present invention;

[0060] Figure 3A three-dimensional structural diagram of the composite resonant cavity structure of the present invention;

[0061] Figure 4 This is a schematic diagram of the composite resonant cavity structure atomic layer TMDs coupled nano-MDM optical cavity structure of the present invention;

[0062] Figure 5 is a schematic diagram of a spectral response measurement system of the present invention;

[0063] Figure 6 This is a temperature-dependent reflection spectrum test diagram of the composite resonant cavity structure (Si / SiO2 / Ag / ITO / WS2 / h-BN / Ag) of the present invention;

[0064] Figure 7 The Fano resonance of the reflection spectrum under temperature tuning observed in the experimental example of the effect of the present invention and its theoretical fitting;

[0065] Figure 8 It is a diagram of the exciton absorption model in the WS2 atomic layer coupled MDM cavity of the present invention;

[0066] Fig. 9 This is an optical microscopic image of the composite resonant cavity structure of the present invention;

[0067] Fig.10 The simulation experiment and theoretical fitting of the Fano resonance multi-field tuning characteristics generated by the composite resonant cavity structure of the present invention;

[0068] Fig.11 Schematic diagram of two-dimensional material peeling;

[0069] Fig.12 Schematic diagram of the two-dimensional material transfer system. DETAILED DESCRIPTION

[0070] To make the purpose, technical solution and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with specific implementation methods and drawings. Unless otherwise specified, the reagents and materials used below are all commercially available products.

[0071] In the following embodiments, the preparation process and test analysis flow chart of the composite resonant cavity structure of MDM nanocavity coupled with two-dimensional transition metal sulfide based on Fano resonance is shown in Figure 1 , the preparation flow chart of each layer is shown in Figure 2 .

[0072] Example 1

[0073] The surface of the silicon wafer substrate is cleaned. The silicon wafer substrate includes a two-layer structure: the thickness of the oxide layer, i.e., the SiO2 layer, is 285±5nm; the thickness of the silicon single crystal, i.e., the Si layer, is 1mm (single-sided oxidation). The specific implementation steps are: ultrasonically clean the silicon wafer substrate in anhydrous ethanol for 10 minutes; ultrasonically clean it in an acetone solution for 5 minutes; soak the silicon wafer substrate in an isopropyl acetone solution for 2 minutes; and finally, use high-pressure nitrogen to flush the surface of the silicon wafer substrate for drying and cleaning.

[0074] Example 2

[0075] Using vacuum evaporation coating equipment, a 31.5 nm thick Ag film was grown on the surface of the SiO2 layer of the silicon wafer substrate after the treatment in Example 1 to obtain a silver layer b. The preparation conditions are: the growth rate should be kept stable, the growth rate should be lower than 0.5 nm / s, and the vacuum degree of the atmosphere in which the silicon wafer substrate is located during the growth period should be less than 10 -5 Pa.

[0076] Example 3

[0077] Using a magnetron sputtering coating device, a 12.5 nm thick indium tin oxide (ITO) thin film was sputtered and grown on the silver layer b obtained in Example 2 to obtain an indium tin oxide layer. The sputtering conditions were: pure argon atmosphere, vacuum degree less than 10 -4 Pa, temperature is 295°C (degrees Celsius), sputtering voltage is 40 volts (V), target material is: ITO; purity is 99.99%; doping ratio: In2O3:SnO2=9:1.

[0078] Example 4

[0079] (1) Fig.11 As shown, a two-dimensional material, namely tungsten disulfide (WS2) layered flakes, is prepared by mechanical exfoliation. The specific implementation steps are: placing a block of two-dimensional material tungsten disulfide on a blue film of a special mechanical exfoliation tape; repeatedly sticking and exfoliating the block material; turning it into a thinner layered flake; transferring the layered flakes on the tape to a flexible substrate PDMS (polydimethylsiloxane) film, and after standing for a period of time, slowly peeling the blue film from the top of the PDMS film, so that the target sample remains on the surface of the PDMS film.

[0080] (2) Transferring the WS2 atomic layer to the surface of the indium tin oxide layer to prepare a tungsten disulfide layer. The specific implementation steps are: using an optical microscope to find the above target sample on the surface of the PDMS film and perform physical and chemical characterization; using a high-precision mechatronic three-axis translation stage in conjunction with a metallographic optical microscope to position and observe to transfer the above target sample to the surface of the ITO film obtained in Example 3 (see the schematic diagram of positioning observation and transfer of the target sample in Fig.12); During the transfer, the attachment / peeling rate of the PDMS film should be as low as possible below 5 μm / s to improve the success rate of mechanical transfer; when the surface of the PDMS film containing the target material is completely attached to the surface of the ITO film, the whole is heated to 60 degrees Celsius for 5 minutes to improve the success rate of the transfer and the surface flatness of the WS2 atomic layer. Finally, the tungsten disulfide layer obtained is 3 layers of WS2 atomic layers.

[0081] Example 5

[0082] (1) Fig.11 As shown, a two-dimensional material, namely hexagonal boron nitride (h-BN) layered flakes, is prepared using a mechanical exfoliation method and attached and retained on the surface of a PDMS film.

[0083] (2) The hexagonal boron nitride layered flakes are transferred to completely cover the surface of the tungsten disulfide layer in Example 4 (see the schematic diagram of the positioning observation and transfer target sample for details). Fig.12 ), forming a coupling region to prepare a hexagonal boron nitride layer. The thickness of the hexagonal boron nitride layer finally obtained is 30 to 55 nm.

[0084] The material used in this embodiment is a block-shaped two-dimensional material hexagonal boron nitride, the transfer target layer is a tungsten disulfide layer, and the rest of the preparation method is the same as the preparation method of the tungsten disulfide layer in Example 4.

[0085] Example 6

[0086] In this embodiment, an 8.5 nm thick Ag film is grown by vapor deposition on the hexagonal boron nitride layer obtained in Example 5. The rest of the preparation methods and conditions are the same as in Example 2 to obtain a silver layer a, and finally an overall composite resonant cavity structure (Si / SiO2 / Ag / ITO / WS2 / h-BN / Ag) of an MDM nanocavity coupled with a two-dimensional transition metal sulfide based on Fano resonance is obtained.

[0087] The three-dimensional structure of the composite resonant cavity structure based on Fano resonance MDM nanocavity coupled with two-dimensional transition metal sulfide is shown in the figure. Figure 3 As shown; d1 / d2 / dw / d3 / d4 / d5 represent Ag / h-BN / WS2 / ITO / Ag / SiO2 respectively, and the actual thicknesses of d1 / d2 / dw / d3 / d4 / d5 are 8.5 / 55 / 2.4 / 12.5 / 31.5 / 285nm respectively; the colored arrows represent the incident and emitted diagrams of the mixed wavelength light beams. Figure 4 The schematic diagram of the atomic layer TMDs coupled nano-MDM optical cavity structure. The relationship between the metal layer, dielectric layer and TMDs is shown in Figure 4 shown.

[0088] Test Case

[0089] The composite resonant cavity structure of the MDM nanocavity coupled with two-dimensional transition metal sulfide based on Fano resonance in Example 6 was taken as a test sample, and spectral measurement and analysis were performed on the sample, and further temperature tuning spectral measurement and analysis, electric field regulation spectral measurement and analysis, etc. were performed.

[0090] Spectral response measurement system such as Figure 5 As shown. The optical response system consists of a light source (Light source), an optical fiber (OF), an optical pinhole (OP), an optical lens (OL), a reflector (M*x, x=*1,2,3,4), a beam splitter (BS), a microscope objective and a spectrometer. The cryogenic sample cavity composite system includes a liquid nitrogen dewar tank and its gas pressure drive device, a three-axis translation stage, a cryogenic sample cavity, a temperature controller and a pinhole molecular pump. The optical response signal acquisition module includes a fiber spectrometer and a focusing component. The sample real-time monitoring and observation system consists of a CCD camera and a monitor.

[0091] First, the entire spectral response measurement system is as follows:

[0092] Module 1 is a spatial optical path. The broadband optical signal generated by the broadband light source is first transmitted through an optical fiber (OF), then beam shaped through an optical pinhole (OP), and collimated by an optical lens (OL) to form a high-quality parallel beam. This beam of parallel light is transmitted to the beam splitter BS-1 under the precise guidance of the reflectors M1 and M2, where it is split. In the light path after beam splitting, one beam of light is focused on the sample surface through the microscope objective, while the other is used as a reference light for calibration. The light beam reflected from the sample surface is collimated by the microscope objective and passes through the second beam splitter BS-2 again. Part of it is directed to the CCD camera connected to the monitor to achieve real-time monitoring of the sample surface, and the other part enters the spectrometer for real-time spectral analysis after precise reflection by the reflectors M3 and M4. In addition, this optical path configuration needs to ensure the precise alignment of the incident light and the reflected light in order to complete the high-precision spectral response measurement based on the original design intention.

[0093] Module 2 is a low-temperature sample chamber system. In order to ensure the stability and controllability of the measurement environment under low temperature conditions, the system is equipped with a reasonably organized system architecture. Among them, the liquid nitrogen dewar tank is used as the main cooling source, and the homemade air pressure drive device and programmable temperature controller are used to achieve precise temperature control with the sample heating stage in the sample chamber; the three-axis translation stage ensures the micron-level precise positioning of the sample position; the molecular pump system maintains the high vacuum environment of the sample chamber, and combined with the homemade molecular pump shock absorber, it can effectively isolate external interference factors.

[0094] Module 3 is a real-time monitoring and observation system, which is completed by a CCD camera and a monitor. It realizes the integration of optical microscopic imaging and real-time measurement of optical response. Through the CCD camera and monitor system, the operator can observe and accurately locate the two-dimensional plane position of the measurement spot on the sample surface in real time. At the same time, the configuration of the high-performance spectrometer enables the system to have spectral analysis capabilities over a wide wavelength range. This integrated design not only significantly improves the accuracy and repeatability of the measurement, but also gives the system the flexibility to adapt to the measurement needs of diverse samples. Especially in the study of temperature dependence, the equipped low-temperature sample chamber system greatly expands the scope of experimental exploration and provides a reliable experimental platform for studying the evolution of the optical properties of two-dimensional materials under different temperature conditions.

[0095] Secondly, the optical response measurement principle of the system is as follows: the system uses the silver mirror reflection method to measure the sample reflectance. This method has a self-calibration characteristic and can effectively eliminate system errors. The entire optical path design fully considers the requirements of beam quality and measurement accuracy. The parameter selection and spatial layout of optical components are optimized to minimize the influence of stray light. When implementing the silver mirror reflectance measurement, the system adopts a standard comparison measurement scheme. The specific process is: first, place the standard silver mirror at the sample position to measure the reflection spectrum and obtain the reference spectrum I0(λ); then replace the sample to be tested to the same position for measurement to obtain the sample reflection spectrum I(λ). Based on the known absolute reflectance R0(λ) of the standard silver mirror, the absolute reflectance of the sample can be obtained by ratio calculation: R(λ)=R0(λ)×[I(λ) / I0(λ)]. The design of this system fully meets the actual test needs of the present invention.

[0096] The obtained temperature-dependent reflection spectrum test graph of the composite resonant cavity structure (Si / SiO2 / Ag / ITO / WS2 / h-BN / Ag) of the present invention is shown in Figure 6 . Figure 6 In the figure, the horizontal axis represents the photon energy (unit: eV), the vertical axis represents the reflectance, and the color gradient represents the ambient temperature of the device under test. Figure 6 In the figure, C1 / C2 / C3 represent the thickness of the dielectric layer h-BN layer, which is 30 / 40 / 55 nm, respectively, and the marking colors are orange / blue / red.

[0097] The Fano resonance of the reflection spectrum under temperature tuning observed in this effect example and its theoretical fitting are shown in Figure 7 , the region is 40nm h-BN (C2, in Fig. 9 (represented by a blue closed line in the figure). Figure 7Middle: (a) is the experimentally measured reflection spectrum of the device structure with temperature change and the Fano theory fitting curve, (b) is a three-dimensional schematic diagram of the resonant cavity structure, (c) is the temperature dependence curve of the Fano quality factor q, (d) is the temperature dependence curve of the Fano resonance center wavelength E0, and (e) is the temperature dependence curve of the Fano resonance line width Γ. The quality factor represents sharpness, that is, the larger the Fano line shape, the sharper it is, and the spectral intensity represents the size measure of the normalized reflection spectrum.

[0098] The diagram of the exciton absorption model in the WS2 atomic layer coupled MDM cavity is shown in Figure 8 . Figure 8 In the figure, C1 / C2 / C3 represent the thickness of the dielectric layer h-BN layer, which is 30 / 40 / 55 nm, respectively, and the marking colors are orange / blue / red.

[0099] The optical microscopic image of the composite resonant cavity structure of the present invention is shown in Fig. 9 . Fig. 9 In the figure, (a) is a structural schematic diagram of the Si / SiO2 / Ag / ITO / WS2 / h-BN / Ag multilayer nanoresonator device and the test principle; (b) is an optical microscopic image of the Si / SiO2 / Ag / ITO / 3L-WS2 / h-BN / Ag multilayer nanoresonator device of the present invention, and the closed curves of different colors represent four different thicknesses of the h-BN layer, denoted as C1 / C2 / C3 / C4, and the corresponding thicknesses are 30nm / 40nm / 55nm / 0nm, respectively, and the colors of the closed curves are orange / blue / red / green, respectively.

[0100] The simulation experiment and theoretical fitting of the Fano resonance multi-field tuning characteristics generated by the composite resonant cavity structure of the present invention are shown in Fig.10 . Fig.10 Middle: (a) is the Y-axis offset simulated reflection spectrum of the Si / SiO2 / Ag / ITO / WS2 / h-BN / Ag structure, (b) is the thickness-dependent reflection spectrum of the dielectric layer (h-BN) of the MDM cavity coupled with a single-layer WS2, (c) is the temperature-thickness-dependent reflection spectrum of the MDM cavity coupled with a single-layer WS2, (d)(e)(f) are the temperature-dependent Fano resonance parameter curves extracted by theoretical fitting, and the vertical axes are the resonance linewidth Γ, the resonance energy center wavelength E0 and the resonance quality factor q, respectively.

[0101] In optical nanoresonators, the coupling of photons and excitons has attracted much attention due to its potential for innovative applications in spectral control. In this paper, an optical resonator is designed by integrating atomically thin tungsten disulfide (WS2) in a metal-dielectric-metal (MDM) nanocavity to manipulate Fano resonances in photonics.

[0102] Therefore, comprehensive Figure 6 , Figure 7 and Fig.10 Data and references Figure 8 , Fig. 9 The diagram is analyzed as follows:

[0103] This effect example uses an independently designed micro-nano-level low-temperature reflection spectrometer to conduct measurement experiments, and observes the temperature-dependent reflection spectrum, which confirms the theoretical performance of the composite resonant cavity structure of the MDM nanocavity coupled with two-dimensional transition metal sulfide based on Fano resonance of the present invention. In the experimental measurement spectrum results, there is an asymmetric spectral response unique to the Fano resonance line ( Figure 6 ). Both experiments and numerical simulations confirm the tunable properties of these tunable asymmetric Fano resonance spectra, which is consistent with theoretical predictions. In addition, the experiments also show that the resonant wavelength and quality factor (q factor) of the composite resonant cavity structure of the MDM nanocavity coupled with two-dimensional transition metal sulfide based on Fano resonance of the present invention can be tuned by temperature or MDM cavity dielectric layer thickness ( Figure 6 , Figure 7 ). The multi-physics spectroscopy simulation of two-dimensional atomic layer TMDs coupled to MDM cavity under different conditions also shows the extension characteristics of the structure ( Fig.10 ).

[0104] In order to analyze the formation mechanism of Fano resonance in this structure, a multilayer electromagnetic medium transmission matrix theoretical model was constructed. Theoretical analysis shows that Fano resonance originates from the coupling between resonant photons in the nanoresonator and excitons in the WS2 layer.

[0105] In summary, the innovation and reliability of the composite resonant cavity structure of the MDM nanocavity coupled with two-dimensional transition metal sulfide based on Fano resonance in the present invention have been fully verified by systematic experiments: a Fano linear reflection spectrum with significant temperature dependence characteristics was obtained through a micro-nano-level low-temperature reflection spectrum measurement system, and the tunable asymmetric response characteristics of Fano resonance in the reflection spectrum were confirmed in the experiment for the first time. The present invention has opened up a new technical path for atomic-level spectral manipulation and exciton-induced Fano resonance modulation, which has important scientific significance and application value.

[0106] The above disclosure is only the preferred embodiment of the present invention, which cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A composite resonant cavity structure of MDM nanocavity coupled with two-dimensional transition metal sulfide based on Fano resonance, characterized in that: The MDM nanocavity includes a dielectric layer and a metal layer; the material of the dielectric layer includes one or more of hexagonal boron nitride and indium tin oxide; and the two-dimensional transition metal sulfide includes tungsten disulfide.

2. According to claim 1, the composite resonant cavity structure of the MDM nanocavity coupled with the two-dimensional transition metal sulfide based on Fano resonance is characterized in that: The MDM nanocavity includes, in sequence: a metal layer a, a hexagonal boron nitride layer, an indium tin oxide layer, and a metal layer b; the material of the hexagonal boron nitride layer includes hexagonal boron nitride; the material of the indium tin oxide layer includes indium tin oxide; the material of the metal layer a includes one or more of silver, titanium, chromium, and gold; the material of the metal layer b includes one or more of silver, titanium, chromium, and gold.

3. The composite resonant cavity structure of the MDM nanocavity coupled with two-dimensional transition metal sulfide based on Fano resonance according to claim 2, characterized in that: The composite resonant cavity structure includes a silver layer a, the hexagonal boron nitride layer, a tungsten disulfide layer, the indium tin oxide layer, and a silver layer b in sequence; the material of the tungsten disulfide layer includes tungsten disulfide; and the materials of the silver layer a and the silver layer b both include silver.

4. The composite resonant cavity structure of the MDM nanocavity coupled with two-dimensional transition metal sulfide based on Fano resonance according to claim 3 is characterized in that: The thickness of the silver layer a is 5 to 15 nm, the thickness of the hexagonal boron nitride layer is 25 to 75 nm, the thickness of the tungsten disulfide layer is 0.7 to 10 nm, the thickness of the indium tin oxide layer is 8 to 20 nm, and the thickness of the silver layer b is 20 to 50 nm.

5. The composite resonant cavity structure of the MDM nanocavity coupled with two-dimensional transition metal sulfide based on Fano resonance according to claim 3, characterized in that: The composite resonant cavity structure also includes a silicon wafer substrate; the silicon wafer substrate includes a SiO2 layer attached to one side of the Si layer; the silicon wafer substrate is attached to the outer side of the silver layer b by the SiO2 layer.

6. A method for preparing a composite resonant cavity structure of an MDM nanocavity coupled with a two-dimensional transition metal sulfide based on Fano resonance according to claim 3, characterized in that: The steps include: S1, growing the silver layer b by vacuum evaporation coating method; S2, growing the indium tin oxide layer on the surface of the silver layer b by magnetron sputtering coating method; S3, preparing the tungsten disulfide layer on the surface of the indium tin oxide layer by a mechanical stripping method; S4, preparing the hexagonal boron nitride layer on the surface of the tungsten disulfide layer by a mechanical stripping method; S5. Growing the silver layer a on the surface of the hexagonal boron nitride layer by a vacuum evaporation coating method to obtain the composite resonant cavity structure.

7. The method for preparing a composite resonant cavity structure of an MDM nanocavity coupled with a two-dimensional transition metal sulfide based on Fano resonance according to claim 6, characterized in that: Step S3 includes the following steps: S3-1, prepare a two-dimensional tungsten disulfide sheet on the surface of the PDMS film, S3-2, transferring the two-dimensional tungsten disulfide sheet to the surface of the indium tin oxide layer to obtain the tungsten disulfide layer; Step S4 includes the following steps: S4-1, prepare a two-dimensional hexagonal boron nitride sheet on the surface of the PDMS film, S4-2, transferring the two-dimensional hexagonal boron nitride sheet to the surface of the tungsten disulfide layer to obtain the hexagonal boron nitride layer.

8. The method for preparing the composite resonant cavity structure of the MDM nanocavity coupled with two-dimensional transition metal sulfide based on Fano resonance according to claim 7, characterized in that: Step S3-1 is specifically as follows: placing a block of tungsten disulfide on an adhesive material, and obtaining a tungsten disulfide layered sheet after repeated adhesion and peeling; then attaching the tungsten disulfide layered sheet to a PDMS film, and peeling off the adhesive material to obtain a two-dimensional tungsten disulfide sheet; Step S3-2 is specifically: attaching the PDMS film to the surface of the indium tin oxide layer, so that the two-dimensional tungsten disulfide sheet is attached to the indium tin oxide layer, and when the PDMS film is completely attached to the surface of the indium tin oxide layer, heating the entire layer; then peeling off the PDMS film to obtain the tungsten disulfide layer; Step S4-1 is specifically as follows: placing a block of hexagonal boron nitride on an adhesive material, and obtaining a hexagonal boron nitride layered sheet after repeated adhesion and peeling; then attaching the hexagonal boron nitride layered sheet to a PDMS film, and peeling off the adhesive material to obtain a two-dimensional hexagonal boron nitride sheet; Step S4-2 is specifically as follows: attaching the PDMS film to the surface of the tungsten disulfide layer, attaching the two-dimensional hexagonal boron nitride sheet to the tungsten disulfide layer, and heating the entire layer when the PDMS film is completely attached to the surface of the tungsten disulfide layer; then peeling off the PDMS film to obtain the hexagonal boron nitride layer.

9. The method for preparing a composite resonant cavity structure of an MDM nanocavity coupled with a two-dimensional transition metal sulfide based on Fano resonance according to claim 6, characterized in that: In step S1, the growth device is a vacuum evaporation coating device; in step S5, the growth device is a vacuum evaporation coating device; in step S1, the growth rate is lower than 0.5nm / s, and the vacuum degree of the growth is less than 10 -5 Pa; in step S5, the growth rate is lower than 0.5 nm / s, and the vacuum degree of the growth is less than 10 -5 Pa; In step S2, the growth equipment is a magnetron sputtering coating equipment; In step S2, the growth conditions include: the atmosphere is pure argon, the vacuum degree is less than 10 -4 Pa, the temperature is 295°C, the sputtering voltage is 40V, and the target material is indium tin oxide; the purity of the target material is 99.99%; the doping ratio of the target material is In2O3:SnO2=9:

1.

10. The method for preparing the composite resonant cavity structure of MDM nanocavity coupled with two-dimensional transition metal sulfide based on Fano resonance according to claim 6, characterized in that: In step S1, the silver layer b is grown on a silicon wafer substrate; the thickness of the SiO2 is 250-350 nm; before step S1, the surface of the silicon wafer substrate is cleaned.

Citation Information

Patent Citations

  • Meta material- microcavity composite structure and preparation method and use thereof

    CN105093777A

  • Biosensing chip and preparation method and application thereof

    CN109946268A

  • Refractive index sensor based on metal nanostructure and single-layer TMDs composite system and method

    CN111896500A

  • Single-particle spectrum electric tuning platform based on two-dimensional material and preparation and regulation methods thereof

    CN114062279A

  • High Quality Factor Metasurfaces for Wavefront Manipulation

    US20240168358A1